Proses Pewarisan Pengetahuan Lokal Dalam Pembuatan Noken Anggrek di Kalangan Perempuan Suku Mee Mapia-Papua - Yanuarius Petege (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to understand the process of transmitting local knowledge in orchid noken making among Papuan women. The research method used was qualitative, using in-depth interviews and participant observation. The results indicate that the process of transmitting local knowledge occurs through direct learning from mothers or grandmothers, and the knowledge passed down includes weaving techniques, designs, and symbolic meanings. This study also demonstrates that Papuan women play a significant role in preserving culture and traditions through orchid noken making. The results of this study can serve as a basis for developing policies and programs that support cultural preservation and the empowerment of Papuan women.